2021
DOI: 10.3389/fcell.2021.673065
|View full text |Cite
|
Sign up to set email alerts
|

Integrating High-Throughput Approaches and in vitro Human Trophoblast Models to Decipher Mechanisms Underlying Early Human Placenta Development

Abstract: The placenta is a temporary but pivotal organ for human pregnancy. It consists of multiple specialized trophoblast cell types originating from the trophectoderm of the blastocyst stage of the embryo. While impaired trophoblast differentiation results in pregnancy disorders affecting both mother and fetus, the molecular mechanisms underlying early human placenta development have been poorly understood, partially due to the limited access to developing human placentas and the lack of suitable human in vitro trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 106 publications
(158 reference statements)
0
6
0
Order By: Relevance
“…We identified that the five TFs (FOS, GATA2, MAFK, TEAD4 and TFAP2C) are also key regulators in mouse TSCs. Since human and mouse placentas have common and distinct characteristics in structure and gene expression patterns ( 17–19 ), we compared the binding sites and the target genes of the five TFs between human and mouse TSCs to dissect the shared and unique functions of these TFs in each species. These TSC-pivotal TFs prefer to bind distal enhancers regardless of their origins (Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified that the five TFs (FOS, GATA2, MAFK, TEAD4 and TFAP2C) are also key regulators in mouse TSCs. Since human and mouse placentas have common and distinct characteristics in structure and gene expression patterns ( 17–19 ), we compared the binding sites and the target genes of the five TFs between human and mouse TSCs to dissect the shared and unique functions of these TFs in each species. These TSC-pivotal TFs prefer to bind distal enhancers regardless of their origins (Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, it is largely unknown to what extent key human TSC-active TFs share their targets and exert conserved or distinct functions between humans and mice. Even though human and mouse placentas play equivalent roles and have numerous functionally conserved genes, there are some discrepancies in their morphology, cellular organization and gene expression patterns ( 17–19 ). Considering these apparent differences, it is necessary to identify human TSC-specific enhancers, TFs and their targets in order to comprehensively understand the regulatory mechanisms underlying human placental development.…”
Section: Introductionmentioning
confidence: 99%
“…During this process, the trophectoderm cells of the blastocyst differentiate into the extravillous trophoblast and the villous trophoblast (comprising the cytotrophoblast and syncytiotrophoblast), which form the major cell lineages of the placenta. Cytotrophoblasts can further differentiate into invasive extravillous trophoblasts ( 32 ). The proliferation and invasion of extravillous trophoblast cells into the decidua and the uterine myometrium are necessary for uterine spiral artery remodeling and establishing maternal-fetal circulation ( 33 ).…”
Section: Establishment and Maintenance Of Early Pregnancymentioning
confidence: 99%
“…Although both mouse and human placentae are discoid in shape with a hemochorial gas–nutrient exchange, mouse model systems do not completely mimic the human placenta, with essential differences including gestational length, litter size, embryo architecture, trophoblast cell types, and tissue organization [ 76 ]. Furthermore, human and mouse TE establishment differ in terms of the expression of some crucial genes during the early development of the two species, as surveyed by [ 77 , 78 , 79 , 80 , 81 , 82 ]. Efforts to obtain human trophoblast stem cells (hTSCs) from blastocysts using culture conditions analogous to murine TSCs have not been successful [ 83 ].…”
Section: Stem Cell-based Trophoblast Modelsmentioning
confidence: 99%